Self-Supporting Sn-Based Carbon Nanofiber Anodes for High-Performance Lithium-Ion Batteries - Jingjie Xie; Lan Xu (Molecules)
Due to its high theoretical specific capacity, abundant resources, accessibility and environmental friendliness, Sn has been considered as a promising alternative to lithium-ion batteries (LIBs) anodes. However, Sn anodes still face great challenges such as huge volume change and low conductivity. Herein, a self-supporting Sn-based carbon nanofiber anode for high-performance LIBs was prepared. Sn-based nanoparticles with high theoretical specific capacity were uniformly embedded in carbon nanofibers, which not only mitigated the volume expansion of Sn-based nanoparticles, but also obtained composite carbon nanofibers with excellent mechanical properties by adjusting the ratio of polyacrylonitrile to polyvinylpyrrolidone, exhibiting excellent electrochemical performance. The obtained optimal self-supporting Sn-based carbon nanofiber anode (Sn-SnO2/CNF-2) showed a discharge specific capacity of 607.28 mAh/g after 100 cycles at a current density of 500 mA/g. Even after 200 cycles, Sn-SnO2/CNF-2 still maintained a capacity of 543.78 mAh/g and maintained its original fiber structure well, demonstrating its good long-term cycling stability. This indicated that the self-supporting Sn-SnO2/CNF-2 anode had great potential for advanced energy storage.